PANTANGAN MASYARAKAT KONJO DALAM PERSPEKTIF GENDER - Suhartina Suhartina; Hasnani Hasnani (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Taboo (Pantangan) is part of the oral tradition Konjo language user community in Bulukumba. The local community still adheres to this tradition. The objectives of this research are to: 1) examine the meaning of the oral tradition of abstinence in the community of Bulukumba Regency, and 2) describe the position of women in the Abstinence tradition in the community of Bulukumba Regency in a gender perspective. Qualitative research involving data gathering techniques such as observation and interviews was used in this study. Transcribing the recorded interview data into written form, classifying data/speech based on the form of oral tradition, translating the speech data into Indonesian; examining the meaning of taboo using anthropolinguistic theory, analyzing based on gender theory and drawing conclusions were all used to analyze the data. The results showed that 1) in textual and contextually taboos in the Konjo language user society in Bulukumba mean a form of avoiding disaster (a form of protection), moral and behavioral protection and maintenance of self-identity and symbols of affection. 2) The position of women in the Bulukumba Regency's abstinence tradition is examined from a gender perspective. Women were in a marginalized position. In the Konjo language-speaking society of Bulukumba, there were certain fundamental disparities between men and women's abstinence. Women were always analogized as weak objects, easy to do wrong things, so they needed to be regulated by